Epidemiology of healthcare harm in New Zealand general practice: a retrospective records review study. Issue 7 (12th July 2021) - Leitch, Sharon; Dovey, Susan; Cunningham, Wayne; Wallis, Katharine; Eggleton, Kyle; Lillis, Steven; McMenamin, Andrew; Williamson, Martyn; Reith, David; Samaranayaka, Ariyapala; Tilyard, Murray
Abstract : Objectives: To determine the epidemiology of healthcare harm observable in general practice records. Design: Retrospective cohort records review study. Setting: 72 general practice clinics were randomly selected from all 988 New Zealand clinics stratified by rurality and size; 44 clinics consented to participate. Participants: 9076 patient records were randomly selected from participating clinics. Intervention: Eight general practitioners examined patient records (2011–2013) to identify harms, harm severity and preventability. Analyses were weighted to account for the stratified sampling design and generalise findings to all New Zealand patients. Main outcome measures: Healthcare harm, severity and preventability. Results: Reviewers identified 2972 harms affecting 1505 patients aged 0–102 years. Most patients (82.0%, weighted) experienced no harm. The estimated incidence of harm was 123 per 1000 patient-years. Most harms (2160; 72.7%, 72.4% weighted) were minor, 661 (22.2%, 22.8% weighted) were moderate, and 135 (4.5%, 4.4% weighted) severe. Eleven patients died, five following a preventable harm. Of the non-fatal harms, 2411 (81.6%, 79.4% weighted) were considered not preventable. Increasing age and number of consultations were associated with increased odds of harm. Compared with patients aged ≤49 years, patients aged 50–69 had an OR of 1.77 (95% CI 1.61 to 1.94), ≥70 years OR 3.23 (95% CI 2.37 to 4.41). Compared with patients with ≤3 consultations, patients with 4–12 consultations had an OR of 7.14 (95% CI 5.21 to 9.79); ≥13 consultations OR 30.06 (95% CI 21.70 to 41.63). Conclusions: Strategic balancing of healthcare risks and benefits may improve patient safety but will not necessarily eliminate harms, which often arise from standard care. Reducing harms considered 'not preventable' remains a laudable challenge.